Chronic kidney disease and mobile health: quality of renal nutritional APPs in Italy - Palmisano, Addolorata; Angileri, Salvatore; Soekeland, Fanny; Gazineo, Domenica; Godino, Lea; Savini, Serenella; Andreoli, Desirèe; Mancin, Stefano (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Patient with chronic kidney disease (CKD) must adhere to a nutritional therapy characterized by a restrictive dietary scheme. Nutritional self-care can be enhanced through the use of nutritional apps. The purpose of this study is to evaluate the characteristics of specific nutritional apps for chronic renal failure available in Italy. Methods: A systematic search of mobile apps was conducted by two academic researchers in three Italian App stores: Google Play Store, Apple Store and Huawei AppGallery. Of the 1602 apps identified, 2 apps (Miku; MyFIR) were evaluated with the Italian version of a Mobile Application Rating Scale (MARS-ITA) by a multidisciplinary team of 20 professionals. Results: The study found that the two selected apps, available in the Google Play Store and Apple Store, aim to increase well-being through the acquisition of knowledge and behavioral change; but none identify health goals that should be achieved. The strategies used by the two applications are: information, education, monitoring and cognitive-behavioral challenge. The technical analysis showed adequate protection of personal data but only the most downloaded app (Miku) provides the possibility to share content, to send reminders and to browse when offline. Conclusions: The main Italian app stores have two applications to monitor physical health and nutrition in patients with renal disease. Although these are free, easily accessible, navigable and valid in terms of health monitoring and information, greater availability of the offer would be desirable.